Enhancing bifunctional catalytic activity of cobalt–nickel sulfide spinel nanocatalysts through transition metal doping and its application in secondary zinc–air batteries. Issue 68 (17th November 2020) - Xu, Yijie; Sumboja, Afriyanti; Groves, Alexandra; Ashton, Thomas; Zong, Yun; Darr, Jawwad A.
Abstract : Transition metal-doped cobalt–nickel sulfide spinel (Ni1.29 Co1.49 Mn0.22 S4 ) nanocatalysts for secondary Zn–air batteries with an efficient and stable electrochemical performance. Abstract : Developing large-scale and high-performance OER (oxygen evolution reaction) and ORR (oxygen reduction reaction) catalysts have been a challenge for commercializing secondary zinc–air batteries. In this work, transition metal-doped cobalt–nickel sulfide spinels are directly produced via a continuous hydrothermal flow synthesis (CHFS) approach. The nanosized cobalt–nickel sulfides are doped with Ag, Fe, Mn, Cr, V, and Ti and evaluated as bifunctional OER and ORR catalyst for Zn–air battery application. Among the doped spinel catalysts, Mn-doped cobalt–nickel sulfides (Ni1.29 Co1.49 Mn0.22 S4 ) exhibit the most promising OER and ORR performance, showing an ORR onset potential of 0.9 V vs. RHE and an OER overpotential of 348 mV measured at 10 mA cm −2, which is attributed to their high surface area, electronic structure of the dopant species, and the synergistic coupling of the dopant species with the active host cations. The dopant ions primarily alter the host cation composition, with the Mn(iii ) cation linked to the introduction of active sites by its favourable electronic structure. A power density of 75 mW cm −2 is achieved at a current density of 140 mA cm −2 for the zinc–air battery using the manganese-doped catalyst, a 12% improvement over the undoped cobalt–nickel sulfide and superior to that of the battery with a commercial RuO2 catalyst.